2002
DOI: 10.1039/b109570f
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer and EPR study of a cytochrome b modelDedicated to Professor F. Dörr on the occasion of his 80th birthday.

Abstract: Mo¨ssbauer and EPR measurements were performed with MOP1, a novel cytochrome b model compound with two heme binding sites. The measurements show for the first site well-resolved normal B-hemichrome EPR signals with characteristic g-values of 2.95, 2.27 and 1.50 which are a feature of the parallel planes orientation of axial histidines. The second site shows a poorly resolved EPR signal with a broad peak at g % 3.5, although both sites are occupied by the same amount of heme as found in the Mo¨ssbauer spectra. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…2A) and EPR spectra (ESI, Fig. S5†) of 2 are indicative of 6-coordinate bis-histidine ligated heme C. 20,21 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A) and EPR spectra (ESI, Fig. S5†) of 2 are indicative of 6-coordinate bis-histidine ligated heme C. 20,21 …”
Section: Resultsmentioning
confidence: 99%
“…Ferric and ferrous UV/visible (Fig.2A) and EPR spectra (ESI, Fig.S5 †) of 2 are indicative of 6-coordinate bis-histidine ligated heme C 20,21. Heme C containing maquette binds O 2 Despite the modications to the original design (1), 2 retains the ability to undergo ligand exchange between the histidine sidechain occupying the 6 th coordination site on heme C and…”
mentioning
confidence: 99%
“…The g zz and A zz are the dominating fine and hyperfine tensor quantities, and this causes the magnetic hyperfine splitting to be determined essentially by the product g zz A zz . It should be noted that Iakovleva et al [63] have reported a heme site in a bisHis coordinated cytochrome b model protein (MOP1), which exhibits an EPR signal similar to those of Type I species, and which they interpreted as a result of a novel spin admixture between the ferric intermediate (S = 3/2) and the low-spin states. However, their Mçssbauer spectroscopic investigation of MOP1 showed that the broadened EPR pattern was caused by spin-spin-relaxation effects between the two heme sites in the model protein.…”
mentioning
confidence: 93%
“…27,28 Studies of the metal center in heme proteins and model systems have shown that many factors, including noncovalent interactions, may play important roles in the properties of these metalloproteins. [29][30][31][32] The importance of CH/p interactions of aromatic residues with porphyrin in hemoproteins was shown. 33 It was demonstrated that the noncovalent interactions with the propionic groups of porphyrins are very important for the orientations of the imidazoles and that the conformations of the propionic groups have a strong influence on these interactions.…”
Section: Introductionmentioning
confidence: 99%